IDENTIFICATION OF BROADLEAF WEEDS IN MATURE COCONUT PLANTATIONS IN TIAL VILLAGE, CENTRAL MALUKU REGENCY, MALUKU PROVINCE, INDONESIA - Tanasale, Vilma Laurien; Kembauw, Esther; Mahulette, Asri Subkhan; Makaruku, Marlita Herlin; Goo, Nureny (Information Technology and Science (ITScience), 2023)
Coconut (Cocos nucifera L.) is a species to be cultivated in Mollucas. Recently, the population of coconut plants has to be decreased as a result of broad leaf weeds that impede the growth of coconut, especially in the nursery phases. The identification of broad leaf weeds is the first step in controlling weeds. However, until now, there has been no research on the influence of broad leaves weed species is important as the base of accurate weed control. This research on broad leaf weed composition in the coconut planting area is important as the base of accuracy is based on Summed Dominance Ratio (SDR) at the production plant in Tial Village, Village Central Mollucas District. This research uses the weed survey method type quadrat method with a sample plot size of 1 m x 1m. The result shows that 13 species of broad leaves weed, 12 families in the areal coconut planting in Tial village